2014
DOI: 10.1002/da.22242
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Postintervention Depression and Disability Outcomes of in-Home Telehealth Problem-Solving Therapy for Depressed, Low-Income Homebound Older Adults

Abstract: Background Despite their high rates of depression, homebound older adults have limited access to evidence-based psychotherapy. The purpose of this paper was to report both depression and disability outcomes of telehealth problem-solving therapy (tele-PST via Skype video call) for low-income homebound older adults over 6 months postintervention. Methods A 3-arm randomized controlled trial compared the efficacy of tele-PST to in-person PST and telephone care calls with 158 homebound individuals who were aged 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
110
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 47 publications
2
110
0
6
Order By: Relevance
“…As such, homebound older adults are socially isolated and at significant risk for loneliness and depression (1,2). While existing interventions promote social integration and activities outside the home for older adults, most homebound older adults are functionally disabled, which limits their opportunity to participate in activities outside the home.…”
Section: Introductionmentioning
confidence: 99%
“…As such, homebound older adults are socially isolated and at significant risk for loneliness and depression (1,2). While existing interventions promote social integration and activities outside the home for older adults, most homebound older adults are functionally disabled, which limits their opportunity to participate in activities outside the home.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies demonstrated the effect of depression treatment on disability in healthy older adults (18, 19), yet there are few large-scale clinical trials investigating the impact of depression treatments on disability in low-income adults with physical limitations. A complexity of treating depression in low-income older adults is the limited access and acceptability of depression treatment.…”
Section: Introductionmentioning
confidence: 99%
“…En un estudio se compararon la psicoterapia presencial y la tele-psicoterapia (a través de llamadas por skype) y se informó que ambos fueron tratamientos eficaces para AM de bajos ingresos; sin embargo, los efectos sobre la depresión y la discapacidad (evaluados por el cambio en la puntuación del WHO-DAS), se mantuvieron por más tiempo en la psicoterapia a distancia en comparación con la presencial 52 . No obstante, el evaluar el efecto de intervenciones conductuales para prevenir o retrasar el inicio o la progresión tanto de la discapacidad como de la depresión en AM, sigue siendo un asunto pendiente.…”
Section: Discussionunclassified